Um caso de pseudo-hermafroditismo em suíno - Rodolpho Torres, José; Côdo, Vitório (Revista Ceres, 1949)
In this work the authors studied a case of pseudo-hermaphroditism occured in swine “Mundi”, a race developed by the Animal Husbandry Department of the Escola Superior de Agricultura do Estado de Minas Gerais, after a 15 year program. The pedigree of the animal showed a consanguinity coefficient of 26.56% above the value for the herd. This close consanguinity is a result of the small number of animals existing in the Animal Husbandry Department.